Mitochondria-Targeted Peptide SS31 Attenuates Renal Tubulointerstitial Injury via Inhibiting Mitochondrial Fission in Diabetic Mice. (2nd June 2019) - Yang, Shi-kun; Li, Ai-mei; Han, Ya-chun; Peng, Can-hui; Song, Na; Yang, Ming; Zhan, Ming; Zeng, Ling-feng; Song, Pan-ai; Zhang, Wei; Tang, Shi-qi; Zhang, Hao
Abstract : Objective . Renal tubular injury is an early characteristic of diabetic nephropathy (DN) that is related to mitochondrial dysfunction. In this study, we explore the effects and mechanisms of mitochondria-targeted peptide SS31 on renal tubulointerstitial injury in DN. Method . 40 C57BL/6 mice were randomly divided into control group, STZ group, STZ+SS31 group, and STZ+normal saline group. SS31 was intraperitoneally injected to the mice every other day for 24 weeks. Renal lesions and the expression of Drp1, Mfn1, Bcl-2, Bax, Caspase1, IL-1 β, and FN were detected. In in vitro studies, HK-2 cells were incubated with different concentrations of D-glucose (5, 30 mM) or combined with SS31 and Drp1 inhibitor Midivi1. Mitochondrial ROS, membrane potential, and morphology have been detected to evaluate the mitochondrial function. Results . Compared with diabetic mice, the levels of serum creatinine and microalbuminuria were significantly decreased in the SS31 group. Renal tubulointerstitial fibrosis, oxidative stress, and apoptosis were observed in diabetic mice, while the pathological changes were reduced in the SS31-treatment group. SS31 could decrease the expression of Drp1, Bax, Caspase1, IL-1 β, and FN in the renal tissue of diabetic mice, while increasing the expression of Mfn1. Additionally, mitochondria exhibit focal enlargement and crista swelling in renal tubular cells of diabetic mice, while SS31 treatment could partially block these changes. An in vitro study showed that pretreatment with SS31 or Drp1 inhibitor Mdivi1 could restore the level of mitochondrial ROS, the membrane potential levels, and the expressions of Drp1, Bax, Caspase1, IL-1 β, and FN in HK-2 cells under high-glucose conditions. Conclusion . SS31 protected renal tubulointerstitial injury in diabetic mice through a decrease in mitochondrial fragmentation via suppressing the expression of Drp1 and increasing the expression of Mfn1.